Potensi Bioakumulator dan Hiperakumulator Lima Spesies Tanaman Sansevieria Berdaun Tebal Terhadap Logam Pb, Cd, Cu dan Zn - Tengku Nurhidayah; Muhammad Ali (Pelantar Press, 2026)
This study critically assesses regional development policies on Sumbawa Island, particularly the PIJAR program (Cattle, Corn, and Seaweed) and the corn nomenclature, through the perspectives of environmental ethics and critical theory. Employing a mixed-method approach, the research integrates a spatial analysis of land cover changes in the Padolo River Basin during 2017-2024 with a policy text examination based on Jürgen Habermas's theory of the